The Implementation of School Regulations in Forming the Disciplined Character of Class X Students at SMK Satria Bhakti Nganjuk - Jatmiko, Jatmiko; Hanif, Muhamad; Malawi, Ibadullah (APPLICATION: Applied science in Learning Research, 2026)
This study aims to describe and explain the implementation of school rules in shaping the disciplinary character of tenth-grade students at SMK Satria Bhakti Nganjuk, as well as to analyze the outcomes of its implementation on changes in student behavior. This research employs a descriptive qualitative approach, with data collected through interviews, observations, and documentation involving the principal, teachers, and students. The data analysis technique used in this study follows the Miles and Huberman model, which consists of three stages: data reduction, data display, and conclusion drawing. The data were analyzed comprehensively and supported with triangulation. The findings of this study indicate that the implementation of school rules that are educative, participatory, and model-based is effective in fostering students’ disciplinary awareness through value habituation, guidance, and moral reflection. Student discipline improved particularly in the aspects of punctuality, wearing uniforms in accordance with regulations, and complying with school policies. This study emphasizes that school rules have the potential to serve as an effective form of character education for developing student discipline when managed consistently and integrated into the school culture.